ANALISIS KONSUMSI BAHAN BAKAR CAMPURAN BENSIN PREMIUM DENGAN â€œCAP-TIKUSâ€ PADA SEPEDA MOTOR SUZUKI SMASH 110 CC - Frisco Lengkong; Hardi Gunawan; Tertius V. Y. Ulaan (JURNAL POROS TEKNIK MESIN UNSRAT, 2013)
Mixing gasoline (premium) with a "Cap-Tikus" is one solution to reduce the consumption of conventional fuels. In this study, testing was conducted on a Suzuki Smash 110 CC motorcycles made â€‹â€‹in 2003 to analyze the fuel consumption for the 2.5 km mileage on gear ratio-2, 3, 4, and velocity 20, 25, 30, 35, 40 km / h with volume mixture of 15% "Cap-Tikus" and 75% gasoline. "Cap-Tikus" used is containing 65% - 90% alcohol (ethanol). Trial of using the gasoline mixed with "Cap-Tikus" is fail to start the engine. Replacing â€œCap-Tikusâ€ with â€œSpiritusâ€ successfully run the engine. It is found that the consumption of the mixture fuel is reducing the consumption of gasoline. The most efficient consumption fuel obtained in the 4th gear using the fuel mixtures are 20.43; 28.64; 38.15; 40.50, and 51.20 g / hr respectively for speed 20, 25, 30, 35 and 40 km / h. Keywords: "cap-tikus", alcohol, fuel consumption, spiritus.